Pelvic lipomatosis: A rare case - Neeraj Agarwal; Krishnendu Maiti (Annals of Medical Science and Research)
Pelvic lipomatosis (PL) is a benign condition characterized by excessive intrapelvic deposition of mature fatty tissue, resulting in compression of pelvic structures and causing a broad range of symptoms. As this condition is rare with limited cases, there are no standardized guidelines for its management. This case of PL was associated with bilateral hydroureteronephrosis and was managed with bilateral percutaneous nephrostomy insertion with long-term follow-up.